Соотношение свободы и безопасности в условиях мультикультурализма - Олійник, І. Г. (ХНУРЕ, 2021)
The article deals with the problems of correlation between the need for freedom and security in the modern information society. It is argued that the satisfaction of these urgent needs can only be achieved by resolving a number of contradictions. The need for security always exists, but it can intensify during periods of exacerbation of the internal situation in society or external threats. The need for freedom most often depends on the level of individual and social development. Solving this problem will require humanity to rise above the needs of today.
Keywords: философия; мультикультурализм